First report of Fusarium incarnatum causing fruit rot of chili pepper in Indonesia - Irda Safni; Lisnawita Lisnawita; Khairunnisa Lubis; Wida Akasah; Nur Ain Izzati Mohd Zainudin; Esraria Simbolon; Namira Istiqomah (Universitas Lampung, 2026)
Chili pepper (Capsicum annuum L.) is a widely cultivated horticultural crop with significant potential as an export commodity. Fruit rot of chili pepper was recorded in Lubuk Cuik village, North Sumatra Province, Indonesia. One hundred and fifty symptomatic fruits were randomly collected from four locations using purposive random sampling. Fungal colonies were isolated from infected fruits until pure cultures were obtained. Pure colonies observed for macroscopic examination exhibited abundant, dense white aerial mycelia with a brown–yellowish base. Microscopic observations revealed numerous long and slender macroconidia, 3–5 septate, with a curved shape and tapering ends. Microconidia were rare, pyriform to obovate in shape, and mostly 0–1 septate. Chlamydospores were thick-walled, intercalary, globose, and produced singly or in chains. Molecular identification was performed using the internal transcribed spacer (ITS) and translation elongation factor (TEF-1α) regions. The pathogenicity of the eight Fusarium incarnatum isolates was tested twice. The morphological characteristics, phylogenetic analysis, and pathogenicity assay confirmed that all isolates were consistent with Fusarium incarnatum. This study represents the first confirmed report of F. incarnatum causing fruit rot of chili pepper in Indonesia.